Murine Models of Nonalcoholic Fatty Liver Disease and Steatohepatitis. (12th December 2012) - Ninomiya, Masashi; Kondo, Yasuteru; Shimosegawa, Tooru
Abstract : In 1980, Ludwig et al. first reported patients of steatohepatitis who lacked a history of excessive alcohol consumption but showed liver histology resembling alcoholic hepatitis and progression to cirrhosis of the liver accompanied by inflammation and fibrosis. The development of nonalcoholic steatohepatitis (NASH) is associated with obesity, diabetes mellitus, insulin resistance, and hyperlipidemia. However, the pathogenesis of NASH remains incomplete. A "multiple-hit" hypothesis for the pathogenesis of NASH based on an animal model has been proposed and remains a foundation for research in this field. We review the important dietary and genetic animal models and discuss the pathogenesis of NASH.